End‐Group Engineering of Chlorine‐Trialkylsiylthienyl Chain‐Substituted Small‐Molecule Donors for High‐Efficiency Ternary Solar Cells. Issue 3 (18th November 2022) - Li, Jing; Zhang, Chenyang; Zhong, Xiuzun; Deng, Wanyuan; Hu, Hanlin; Wang, Kai
Abstract: Ternary architecture has been widely demonstrated as a facile and efficient strategy to boost the performance of organic solar cells (OSCs). However, the rational design of the third component with suitable core and end‐group modification is still a challenge. Herein, two new small‐molecule (SM) donors BT‐CN and BT‐ER, featuring the identical conjugated backbone with distinct end group, have been designed, synthesized, and introduced into the PM6:Y6 binary system as the second donor. Both molecules exhibit complementary absorption and good miscibility with PM6, contributing to the nanofibrous phases and strong face‐on molecular packing. Importantly, the incorporation of BT‐CN/BT‐ER has significantly facilitated charge collection and transportation with remarkable suppression of carrier recombination. As a result, ternary OSCs with 20 wt% BT‐CN/BT‐ER achieved a PCE of 16.8%/17.22% with synchronously increased open‐circuit voltage ( V OC ), short‐circuit current density ( J SC ) and fill factor (FF). Moreover, replacing Y6 with L8‐BO further improves the PCE to 18.05%/18.11%, indicating the universality of both molecules as the third component. This work demonstrates not only two efficient SM donors with 4, 8‐bis(4‐chloro‐5‐(tripropylsilyl)thiophen‐2‐yl) benzo[1, 2‐ b :4, 5‐ b′ ]dithiophene (BDTT‐SiCl) as the core but also end group modification strategy to fine‐tune the absorption spectrum, molecular packing, and energy levels of SM donors to construct high‐performance ternary OSCs. Abstract : Two small molecule donors BT‐CN/BT‐ER with different end groups are synthesized and introduced into the blend film of PM6:Y6. The result ternary OSCs with 20 wt.% BT‐CN/ BT‐ER achieves a PCE of 16.8%/17.2%, receptively. When replacing Y6 with L8‐BO, ternary devices incorporating these two SM donors both reach PCE of over 18%, indicating the universality of these two SM donors as the third component for highly efficient PM6‐based ternary OSCs.